2012
DOI: 10.1080/10401334.2012.715261
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Medical Students Studying in New Zealand: A Comparison With Nonmedical Students and a General Population Reference Group

Abstract: The results suggest that all university students are expressing concerns related to quality of life, and thus their health might be at risk. The findings in this study provided no evidence to support the notion that medical students experience lower levels of quality of life compared to other university students. When compared to the general population, all student groups examined in this study appeared to be experiencing lower levels of quality of life. This has implications for pastoral support, educationali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 30 publications
4
46
1
6
Order By: Relevance
“…However, there are no definite results demonstrating that medical students are basically more burdened by psychological morbidity during their studies than other high-achieving student populations. Henning et al [12], for example, indicated that medical students have a similar quality of life in terms of physical and psychological health as non-medical students. In contrast, Aktekin et al [13] showed a higher psychological distress in medical students compared to students studying economics and physical education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no definite results demonstrating that medical students are basically more burdened by psychological morbidity during their studies than other high-achieving student populations. Henning et al [12], for example, indicated that medical students have a similar quality of life in terms of physical and psychological health as non-medical students. In contrast, Aktekin et al [13] showed a higher psychological distress in medical students compared to students studying economics and physical education.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the general population, there is a clear indication that burnout and low physical and psychological health is more prevalent among physicians at each stage of their career [5, 12]. In order to address the impending risk of developing mental health problems during training and in later professional life, health promotion and prevention programs have become prevalent in medical schools.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study noted that medical students' quality of life was worse than that of the general population. 8 We can scarcely wonder why students choose career specialties based on the perceived lifestyle associated with the specialties. 9 We need to help medical students put their short-term and long-term objectives into perspective.…”
mentioning
confidence: 99%
“…Among others, these include dealing with topics like life and death, illness and suffering, the perception one’s physical and emotional limitations, problems in private life and financial matters. Consequences could result in a higher burden of anxiety and depression [1], [2] and a lower quality of life in comparison to students of other disciplines and the general population [3], respectively. Substantive and structural conditions of the curricula can favor the occurrence of these burdens [4], [5] and even intensify them over time [6].…”
Section: Introductionmentioning
confidence: 99%